2012
DOI: 10.1179/1476830512y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of α-mangostin and curcumin against iodoacetate-induced cell death

Abstract: Treatment with α-mangostin and curcumin provided a neuroprotective effect against IAA in primary cultures of CGNs, an effect associated with an amelioration of the IAA-induced ROS production. HO-1 induced by these antioxidants may also be involved in the neuroprotective effect. Future work will be required to determine whether α-mangostin may cross the blood-brain barrier and achieve enough bioavailability to elicit a protective response in the brain being an effective nutraceutical compound for preventive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 23 publications
0
34
2
Order By: Relevance
“…When the diet of gerbils was supplemented with curcumin for 2 months and they were then subjected to transient global cerebral ischemia, death of CA1 hippocampal neurons was significantly less than in gerbils that did not receive curcumin (Wang et al, 2005a). Curcumin protected cultured neuronal cells against death induced by iodoacetate, an inhibitor of glycolysis (Reyes-Fermín et al, 2012). Curcumin treatment also reduced neuronal and microvessel degeneration in the retina in a rat model of ischemiareperfusion injury (Wang et al, 2011c).…”
Section: B Metabolic Stressmentioning
confidence: 99%
“…When the diet of gerbils was supplemented with curcumin for 2 months and they were then subjected to transient global cerebral ischemia, death of CA1 hippocampal neurons was significantly less than in gerbils that did not receive curcumin (Wang et al, 2005a). Curcumin protected cultured neuronal cells against death induced by iodoacetate, an inhibitor of glycolysis (Reyes-Fermín et al, 2012). Curcumin treatment also reduced neuronal and microvessel degeneration in the retina in a rat model of ischemiareperfusion injury (Wang et al, 2011c).…”
Section: B Metabolic Stressmentioning
confidence: 99%
“…Xanthones from Callophyllum brasiliense Cambess have shown to be inhibitors of sulfotransferases, SULT1A1 and SULT2A1 [14], antibiotics [15], and inhibitors of gastric H + , K + −ATPase activity [16]. Furthermore, it has been reported that xanthones from other sources, like α-mangostin, are effective antioxidants and could be important free radical scavengers [17-21]. This study was conducted to explore the scavenging effects and antioxidant properties of xanthones III and V (Figure 1b and 1c, respectively) isolated from Callophylum brasiliensis, a species collected in the Mexican rain forest.…”
Section: Introductionmentioning
confidence: 99%
“…Since estrogen plays a vital role in the development and progression of hormone-responsive breast cancers, α-MGʼs suppressive effect on CYP19/aromatase indicates its potential as a chemopreventive or a chemotherapeutic agent in mammary carcinogenesis. Importantly, it was reported that in a concentration-and time-dependent way, α-MG treatment increased the protein level and activity of HO-1, an important cytoprotective protein induced during the phase II response [35]. Currently, however, studies regarding the effects of α-MG on phase I and II enzymes and the involved signaling pathways are limited, which warrant further investigations.…”
Section: Modulation Of Phase I and Phase Ii Enzymesmentioning
confidence: 95%
“…Mammary tumorigenesis↓, CYP1A1↓, CYP1A2↓, CYP1B1↓ Ex vivo mouse mammary organ culture assay [33] CYP19/aromatase activity↓ Microsomal [34] Protein expression and activity HO-1 ↑ Cerebellar granule neurons [35] Antioxidant aSMase activity↓ Enzyme derived-bovine brain [56] Making SOD, GPx, CAT recover to normal level Isoproterenol-induced myocardial infarction [38] Attenuation of inflammation NO release↓, PEG2 release↓, iNOS expression↓, COX-2 expression↓ LPS-stimulated RAW264.7 macrophage cells [61,62] Protein and mRNA expressions of COX-2↓, PEG2↓ Human breast cancer MDA-MB-231 cells [64] Direct interaction with COX-2 and iNOS Molecular modeling and docking study [65] SIRT-1↑, p65/NFκB acetylation↓, COX-2 expression↓, iNOS expression↓, NO production↓, PEG2 level↓ LPS-stimulated U937 cells [67] Induction of cell cycle arrest cyclinD1/CDK4 expression↓, p27KIP1 expression↑, cyclinE expression↓, phosphorylated Rb expression↓ direct interaction with CDK4…”
Section: Modulation Of Phase I and Ii Enzymesmentioning
confidence: 99%